Harnessing the Natural Healing Power of Colostrum: Bovine Milk‐Derived Extracellular Vesicles from Colostrum Facilitating the Transition from Inflammation to Tissue Regeneration for Accelerating Cutaneous Wound Healing. Issue 6 (16th December 2021) - Kim, Hyosuk; Kim, Da Eun; Han, Geonhee; Lim, Nu Ri; Kim, Eun Hye; Jang, Yeongji; Cho, Haeun; Jang, Hochung; Kim, Ki Hun; Kim, Sun Hwa; Yang, Yoosoo
Abstract: As wound healing is an extremely complicated process, consisting of a cascade of interlocking biological events, successful wound healing requires a multifaceted approach to support appropriate and rapid transitions from the inflammatory to proliferative and remodeling phases. In this regard, here the potential use of bovine milk extracellular vesicles (EVs) to enhance wound healing is investigated. The results show that milk EVs promote fibroblast proliferation, migration, and endothelial tube formation. In particular, milk EVs derived from colostrum (Colos EVs) contain various anti‐inflammatory factors facilitating the transition from inflammation to proliferation phase, as well as factors for tissue remodeling and angiogenesis. In an excisional wound mouse model, Colos EVs promote re‐epithelialization, activate angiogenesis, and enhance extracellular matrix maturation. Interestingly, Colos EVs are further found to be quite resistant to freeze‐drying procedures, maintaining their original characteristics and efficacy for wound repair after lyophilization. These findings on the superior stability and excellent activity of milk Colos EVs indicate that they hold great promise to be developed as anti‐inflammatory therapeutics, especially for the treatment of cutaneous wounds. Abstract : The potential use of milk extracellular vesicles (EVs) to enhance wound healing is investigated. Milk EVs, especially derived from colostrum contain a cocktail of anti‐inflammatory cytokines and factors for tissue remodeling, facilitating the inflammatory‐tissue regeneration phase transition of wound healing. Based on their superior stability and excellent activity, milk EVs hold infinite promise to be developed as anti‐inflammatory therapeutics.